Aplicación de instrumentos sobre niñez apátrida (2022)
The Colombian State has within its obligations, the design of public policies that lead to the protection and respect of fundamental rights, among these obligations we can find the recognition of the nationality of all people born within Colombian territory, but it is also in the obligation to watch over those agents who, although they were not born in Colombian territory, seek to be recognized as nationals or at least have access to basic and essential services, such as food, education or public services. This research project seeks to identify those public policies, actions or procedures that allow the Colombian State to ensure and will be the guarantor of the protection of these Fundamental Rights and the special protection of national or foreign children and adolescents who are in the Colombian territory.